2001
DOI: 10.1161/hc3901.095769
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Endothelial Nitric Oxide Synthase Expression in the Vascular Wall and in Mononuclear Cells From Hypercholesterolemic Rabbits

Abstract: Background-We recently obtained evidence demonstrating that cultured bovine endothelial cells contain cytosolic proteins that form complexes with the 3Ј-untranslated region of endothelial nitric oxide synthase (eNOS) mRNA and are associated with its destabilization. The aim of this study was to determine the presence of such proteins and eNOS expression in hypercholesterolemic rabbits as an in vivo model of endothelial dysfunction. Methods and Results-Endothelium-dependent relaxation to acetylcholine and the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 33 publications
2
32
0
Order By: Relevance
“…[8][9][10]25 In the present study, we have demonstrated that pericardial cytosolic lysates form complexes with the complete in vitrotranscribed 3Ј-UTR of eNOS mRNA. Furthermore, cytosolic lysates obtained from LPS-and SA-incubated pericardial samples showed an increased binding activity to 3Ј-UTR of eNOS mRNA, which was associated with a decreased level of eNOS protein and eNOS mRNA expression.…”
Section: Discussionsupporting
confidence: 54%
“…[8][9][10]25 In the present study, we have demonstrated that pericardial cytosolic lysates form complexes with the complete in vitrotranscribed 3Ј-UTR of eNOS mRNA. Furthermore, cytosolic lysates obtained from LPS-and SA-incubated pericardial samples showed an increased binding activity to 3Ј-UTR of eNOS mRNA, which was associated with a decreased level of eNOS protein and eNOS mRNA expression.…”
Section: Discussionsupporting
confidence: 54%
“…Moreover, supplementation with L -arginine, the precursor of NO, reverses endothelial dysfunction in otherwise healthy young humans with hypercholesterolemia [22] . The reduction in NO bioavailability observed in hypercholesterolemic patients [23,24] could be related to various mechanisms, among them: (1) a decrease in endothelial NO synthase (eNOS) expression (mRNA and protein levels) in response to oxidized LDLs (oxLDLs) and atherogenic concentrations of native LDLs (nLDLs) has been described in vivo [25] and in vitro [13,14,17] ; (2) an increase in caveolin-1 and the inactive complex caveolin-1/eNOS, has been reported in endothelial cells treated with sera from hypercholesterolemic patients , has been observed ex vivo in vessels from hypercholesterolemic animals [27] ; (4) the uncoupling of eNOS activity produced by oxLDL and atherogenic concentrations of nLDLs that reduce the association between eNOS and hsp90 and increases the generation of O 2 -have been reported [28,29] ; (5) the reduction of eNOS activity as a consequence of the inhibitory effect of asymmetric dimethylarginine (ADMA), whose levels are increased in hypercholesterolemic patients [30] or (6) the impairment of L -arginine uptake by endothelial cells produced by both nLDLs and oxLDLs [29] .…”
Section: Hypercholesterolemia-induced Endothelial Dysfunction: Impairmentioning
confidence: 99%
“…Considering hyperlipidemia and atherosclerosis, aortic segments of hypercholesterolemic rabbits show significant reduction of endothelial nitric oxide synthase (NOS) in relation to controls 17 . Vasquez-Vivar et al 18 reported that BH4, a cofactor for the synthesis of NO in the aorta of rabbits fed a hypercholesterolemia-inducing diet, was markedly reduced in comparison to normocholesterolemic rabbits.…”
Section: Introductionmentioning
confidence: 99%